2022
DOI: 10.9734/ijbcrr/2022/v31i330309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant-Based Biotin from SesZenBioTM and In silico Studies to Prove Its Potential in Hair Care

Abstract: A standardized extract from Sesbania agati leaves (SESAL) was developed by Zenherb labs Pvt. Ltd., Mumbai, and is one of its kind plant-based biotin supplements.  The current work aimed at characterization of SESAL using chromatographic techniques (like HPLC & HPTLC) and DNA authentication. Additionally, an in-silico approach (docking) was also adopted to predict the molecular interactions and probable mechanisms involved in potential role of SESAL in hair care products range.  Drug likeliness was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In silico testing suggested that test treatment enhances hair follicle growth and improve hair health. 19 In a survey of 900 physicians, including 300 dermatologists, 66% of dermatologists stated recommending dietary supplements to their patients to improve their skin and hair health. 23 Hair loss conditions are multifactorial, ranging from improper nutrition, environmental factors causing stress to hormonal imbalances, inflammation, drug use and many more.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In silico testing suggested that test treatment enhances hair follicle growth and improve hair health. 19 In a survey of 900 physicians, including 300 dermatologists, 66% of dermatologists stated recommending dietary supplements to their patients to improve their skin and hair health. 23 Hair loss conditions are multifactorial, ranging from improper nutrition, environmental factors causing stress to hormonal imbalances, inflammation, drug use and many more.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The leaves and flowers of Agati are abundant in vitamins (biotin, A, C, B2, etc) and minerals (zinc and selenium), whereas the bark and flowers are rich in polyphenols. 19 Biotin, alternatively recognized as Vitamin B7 or H (with H derived from "Haar und Haut," German for "hair and skin"), is a water-soluble B vitamin serving as a crucial cofactor for numerous carboxylases which play pivotal role in the cellular metabolism of fatty acids, amino acids, and gluconeogenesis. 20 Due to its affordability and widespread availability, biotin has emerged as an effective solution for hair health, promoting longer and healthier growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation